Anatomy & physiology : - Saladin, Kenneth S. (McGraw-Hill Higher Education, 2004)
This distinctive text was developed to stand apart from all other anatomy and physiology texts with a unique approach, unparalleled art, and a writing style that has been acclaimed by both users and reviewers. Designed for a two-semester A&P college course, Saladin requires no prior knowledge of college chemistry or cell biology.